Economic and environmental aspects of introducing the use of biodiesel in the hospitality and tourism business of rural Istria - Ružić, Pavlo; Ružić, Ivan, ekonomist; Dropulić Ružić, Marinela (2008)
Abstract: This paper looks on possibility of induction biodiesel fuel in tourism business. According to that, authors research economical and ecological impacts of biodiesel fuel on tourism business and environmental protection. In work, authors give answers about general characteristics of biodiesel fuel, and make comparison with classic diesel fuel. Researching issue are also production process and prices and what kind of effects brings induction of biodiesel fuel on economy of tourism and ecology. From that point of view, authors set up hypothesis that induction of biodiesel fuel in tourism business can obtain increasing in economical view and bring environmental protection of tourist destination. In paper are used methods for researching social, economical and ecological impacts of biodiesel fuel on tourism business development
Bibliografske bilješke uz tekst ; bibliografija: 6 jed
Keywords: Biodizelska goriva -- Primjena -- Hrvatska